2015
DOI: 10.1159/000368507
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Uric Acid Levels and Intrarenal Hemodynamic Parameters

Abstract: Background/Aims: Hyperuricemia has been reported to affect renal hemodynamics in rat models. We evaluate the relationship between serum uric acid and intrarenal hemodynamic parameters in humans, utilizing the plasma clearance of para-aminohippurate (CPAH ) and inulin (Cin). Methods: Renal and glomerular hemodynamics were assessed by simultaneous measurement of CPAH and Cin in 58 subjects. Of these, 19 subjects were planned to provide a kidney for transplantation; 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…In recent years attention has focused on high serum uric acid as a potential risk factor for cardiorenal disease [22][23][24][25]. However, a low serum uric acid due to high fractional excretion may also be relevant to renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years attention has focused on high serum uric acid as a potential risk factor for cardiorenal disease [22][23][24][25]. However, a low serum uric acid due to high fractional excretion may also be relevant to renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SUA induced oxidative stress and endothelial dysfunction may result in the development of both systemic and glomerular hypertension, which would reduce renal blood flow and elevate renal vascular resistance [25,26]. Uedono et al [27] also found that SUA levels was significantly and independently associated with the vascular resistance at the afferent arteriole. In addition, SUA may stimulate vascular smooth muscle cell proliferation through the activation of the renin-angiotensin system [28].…”
Section: Serum Uric Acid and Chronic Kidney Diseasementioning
confidence: 99%
“…Although this result was in contrast to remains to be established. Hyperuricemia is also well known to be associated with hypertension, endothelial dysfunction and development of cardiovascular and kidney diseases [24][25][26][27]. Previous studies suggested that uric acid induces proliferation of vascular smooth muscle cells, activates the renin-angiotensin-aldosterone system and also reduces the synthesis of nitric oxide; while at the same time increases inflammation and oxidative stress [26,28,29].…”
Section: Associations Between C3 Staining Clinical and Laboratory Fementioning
confidence: 99%